The Concept of Motherly Love in Margaret Widdemer’s“The Watcher” - Pertiwi, Vina (LANTERN (Journal on English Language, Culture and Literature), 2016)
Margaret Widdemer’s “The Watcher” tells about how the watcher has wonderful love to her beloved. The purpose of this study is to analyze the intrinsic elements of the poem and the kind of love in the poem. The writer uses psychological approach to prove that the love in this poem is between mother and her childrenbased on Erich Fromm’s theory of love.The writer uses library research in her study for collecting the data. The writer obtained the data and information related to the object from the books and internet source. The result of this study shows that the poem talks about the love of mother to her children. It can be categorized into motherly love.